STRATEGI PENGEMBANGAN USAHA SAMBAL IKAN ROA PADA INDUSTRI âCITARASAKUâ KELURAHAN TINGGEDE KECAMATAN MARAWOLA KABUPATEN SIGI - Haryanto, Malan; Rauf, Rustam Abd (AGROTEKBIS, 2017)
This study aims to determine the business development strategies of fish sambal roa right Â Â to apply to Industry "Citarasaku" Tinggede Village District of Marawola Sigi. This research Â Â Â Â Â Â Â Â was conducted in September to October 2015, the number of respondents as many as six people. The analysis tool used is the SWOT analysis, by analyzing internal and external factors of the industry Citarasaku ". The based on the results of SWOT analysis that the position of industrial strategy" Citarasaku "is at kuadran I is at position strategy Strengths - Opportunities (SO), the result showed some business development strategies roa sauce fish appropriate to be applied in the industry "Citarasaku" ie (a) Utilizing the availability of raw materials to increase production in order to capture opportunities in high demand, (b) Utilizing packaging attractive products and prices affordable products in order to capture opportunities through the rapid development of the media campaign, (c) Continue to maintain the quality of their products in order to capture opportunities from the government through the assistance and activities organized by the government as an exhibition.Â Key Words : Citarasaku, strategy development, SWOT Analysis.Â